Flooding events turned into farming opportunities: Innovation transforms livelihoods of pastoralists in Ethiopia - Amede, Tilahun; Akker, Elisabeth van den; Berdel, Wolf; Ketter, Christina; Tilahun, Gebeyaw; Dejen, Asmare; Legesse, Gizachew; Abebe, Hunegnaw; Getnet, Mezgebu (2019)
• Water Spreading Weirs: To capture and spread the torrential flood emerging in the neighboring highlands to low-lying rangelands and crop fields, five weirs were built based on land suitability studies. • Working together: Joint planning and execution between community leaders, landscape and crop researchers and development agents using a combination of good agronomy, remote sensing and GIS-based maps yielded positive results. • Success draws attention: Seeing the results, pastoralists were willing to take up farming. It created local confidence, drew government attention and benefited pastoralists.